2004
DOI: 10.1099/ijs.0.02832-0
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiopsis alkaliphila sp. nov., a novel alkaliphilic actinomycete isolated from desert soil in Egypt

Abstract: An alkaliphilic actinomycete strain, designated YIM 80379T, was isolated from a soil sample collected from the eastern desert of Egypt and subjected to polyphasic taxonomy. The strain produced substrate and aerial mycelia on different media, with an optimum pH for growth of 9·5–10 and scarce or no growth at pH 7. Strain YIM 80379T contained meso-diaminopimelic acid, no diagnostic sugars, type PIII phospholipids and MK-10(H6) and MK-10(H8) as the predominant menaquinones. All of these characters assign isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 39 publications
1
33
1
1
Order By: Relevance
“…dassonvillei (Meyer, 1976), N. alba, N. listeri (Grund & Kroppenstedt, 1990), N. halophila (Al-Tai & Ruan, 1994), N. lucentensis (Yassin et al, 1993), N. prasina, N. synnemataformans (Yassin et al, 1997), N. kunsanensis (Chun et al, 2000), N. tropica, N. trehalosi, N. dassonvillei subsp. albirubida (Evtushenko et al, 2000), N. exhalans, N. umidischolae (Peltola et al, 2001), N. halotolerans (Al-Zarban et al, 2002), N. composta (Kämpfer et al, 2002), N. metallicus (Schippers et al, 2002), N. xinjiangensis (Li et al, 2003), N. alkaliphila (Hozzein et al, 2004), N. salina , N. aegyptica (Sabry et al, 2004), N. baichengensis, N. chromatogenes, N. gilva, N. rhodophaea and N. rosea (Li et al, 2006). Most species are alkaliphilic or halophilic.…”
mentioning
confidence: 99%
“…dassonvillei (Meyer, 1976), N. alba, N. listeri (Grund & Kroppenstedt, 1990), N. halophila (Al-Tai & Ruan, 1994), N. lucentensis (Yassin et al, 1993), N. prasina, N. synnemataformans (Yassin et al, 1997), N. kunsanensis (Chun et al, 2000), N. tropica, N. trehalosi, N. dassonvillei subsp. albirubida (Evtushenko et al, 2000), N. exhalans, N. umidischolae (Peltola et al, 2001), N. halotolerans (Al-Zarban et al, 2002), N. composta (Kämpfer et al, 2002), N. metallicus (Schippers et al, 2002), N. xinjiangensis (Li et al, 2003), N. alkaliphila (Hozzein et al, 2004), N. salina , N. aegyptica (Sabry et al, 2004), N. baichengensis, N. chromatogenes, N. gilva, N. rhodophaea and N. rosea (Li et al, 2006). Most species are alkaliphilic or halophilic.…”
mentioning
confidence: 99%
“…While most of the studies are concerned with the molecular phylogeny of halo-tolerant and alkaliphilic actinomyces (6,10,14,18,19), the similar attention has not been paid to their enzymology. However, the ability to produce a variety of enzymes may be an attractive phenomenon in these prokaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of writing, the taxon encompasses 24 recognized species (Li et al, 2006), which form a distinct clade within the evolutionary radiation occupied by members of the family Nocardiopsaceae (Rainey et al, 1996;Cui et al, 2001;Kroppenstedt & Evtushenko, 2006). Nocardiopsis strains are frequently isolated from saline and alkaline soils (Li et al, , 2006Hozzein et al, 2004), but have also been recovered from an alkaline slag dump (Schippers et al, 2002), clinical material (Yassin et al, 1997;Mordarska et al, 1998), indoor environments (Peltola et al, 2001), the atmosphere of a composting facility (Kämpfer et al, 2002) and a marine sediment (Sabry et al, 2004). In the present polyphasic study, an actinomycete isolated from a sand-dune soil was shown to represent a novel species of the genus Nocardiopsis.…”
mentioning
confidence: 99%